The Use of Plastic Ankle-Foot Orthosis Prescribed for Patients with Foot Drop: The Application and Related Factors - Poolpipat, Panida; Suksathien, Rachawan (ASEAN Journal of Rehabilitation Medicine, 2023)
Objectives: To study the use patterns and factors related to the use of thermoplastic ankle-foot orthoses (AFO) by patients with foot drop to provide information and to help develop more efficient methods for making decisions regarding the prescription of AFOs. Study design: Cross-sectional study. Setting: Department of Rehabilitation Medicine, Maharat Nakhon Ratchasima Hospital. Subjects: Patients with foot drop who had received thermoplastic AFOs between January 2021 and March 2022. Methods: Demographics and clinical data were collected from the medical records of the patients. Frequency, duration, and other data related to AFO use were collected via phone interviews with the patients after the AFO had been prescribed for at least 3 months. Use of the AFO was defined as continuous use at least one day a week. Factors associated with compliance with recommended AFO use was analyzed using multivariable analysis. Results: This study included 117 patients (77 men) with a meanage of 52 years. Of those patients, 59.8% reported continuous use of the AFO with a 95% confidence interval (CI) of 50.8-68.8. Patients who were unable to do ankle dorsiflexion, who wore clogs and who practiced walking with a physical therapist were more likely to use an AFO with adjusted prevalence ratios (95% CI) of 1.49 (1.04-2.14), 1.75 (1.05-2.93), and 1.45 (1.06-1.98), respectively. Conclusions: Sixty percent of foot drop patients continued using an AFO after 3 months. Half of those patients used the AFO every day. Being unable to do ankle dorsiflexion, wearing clogs, and practicing walking with a physical therapist were all associated with good compliance with AFO use.